Productive Development Policies in Jamaica - Monica Panadeiros; Warren Benfield (Inter-American Development Bank (IDB), 2010)
Jamaica seems to be a puzzling case for economic growth: despite the structural reforms implemented in the last three decades and adequate investment levels, real GDP per capita is roughly the same as in 1970. The disappointing performance of this economy suggests that productive development policies (PDPs), including first-generation reforms, have not been enough to create a better environment for productivity growth. This paper examines the PDPs in Jamaica and concludes that behind the paradox of high investment and low growth of this economy are the public debt trap and a highly distortive tax incentive structure to attract foreign direct investment (FDI) and promote exports. Although industrial policy is moving towards a more modern conceptual design, the old schemes seem politically difficult to dismantle.
Keywords: L52; O25; O54; 330; Productivity; Industrial policy; Foreign direct Investment; Jamaica